Ivarmacitinib improves patient-reported outcomes across multiple domains in patients with active ankylosing spondylitis: a post hoc analysis of a phase II/III trial - Xu, Xiaoyan; Wei, Hua; Liu, Linchen; Yang, Rong; Shi, Qing; Pang, Dandan (Frontiers in Pharmacology, 2025)
BackgroundIvarmacitinib (SHR0302), a selective Janus kinase 1 inhibitor, has demonstrated substantial improvements in patients with active ankylosing spondylitis (AS). This post hoc analysis evaluated the effects of ivarmacitinib on various dimensions of patient-reported outcomes (PROs) in active AS patients, utilizing data from a phase II/III clinical trial (NCT04481139).MethodsPatients were assigned to receive either ivarmacitinib 4 mg (n = 187) or placebo (n = 186) daily for 12 weeks. Patients receiving placebo switched to ivarmacitinib thereafter until week 24. PROs included total back pain and night pain by visual analog scale (VAS), morning stiffness, Patient Global Assessment of Disease Activity (PtGA), AS Quality of Life (ASQol), 36-Item Short Form Health Survey (SF-36), Bath AS Disease Activity Index (BASDAI), and Bath AS Functional Index (BASFI).ResultsIvarmacitinib group showed significantly improvement in total back pain VAS (P < 0.001), night pain VAS (P < 0.001), morning stiffness (P < 0.001), PtGA (P < 0.001), ASQoL (P = 0.034), and BASDAI (P < 0.001) scores compared with placebo after 12 weeks of treatment. However, no significant between-group differences were observed for SF-36 physical scores (P = 0.216), mental (P = 0.105) component scores and BASFI score (P = 0.744) at week 12. By week 24, all PROs were continuously improved in the ivarmacitinib group; patients who switched from placebo to ivarmacitinib 4 mg achieved substantial improvements in all PROs.ConclusionIvarmacitinib significantly enhances multiple dimensions of PROs in active AS patients, supporting its utility in managing PROs in AS. Switching to ivarmacitinib also provides substantial benefits, this indicates that initiating ivarmacitinib treatment, even after an initial period of placebo leads to meaningful improvements in PROs.